What fresh hell is this? : perimenopause, menopause, other indignities, and you - Corinna, Heather (Hachette Go, 2021)
"An informative, blisteringly funny, somewhat cranky and always spot-on guide to perimenopause and menopause by the award-winning sex ed/health educator and author of S.E.X."--